2022
DOI: 10.3389/fphar.2022.794277
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum-Effect Relationship Analysis of Bioactive Compounds in Zanthoxylum nitidum (Roxb.) DC. by Ultra-High Performance Liquid Chromatography Mass Spectrometry Coupled With Comprehensive Filtering Approaches

Abstract: Zanthoxylum nitidum (Roxb.) DC. (ZN), with strong effects of anti-inflammation and antioxidant activities is treated as a core herb in traditional Chinese medicine (TCM) preparation for treating stomachache, toothache, and rheumatoid arthritis. However, the active ingredients of ZN are not fully clarified due to its chemical complexity. In the present study, a double spectrum–effect analysis strategy was developed and applied to explore the bioactive components in herbs, and ZN was used as an example. Here, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…When the CH 2 O group (30 Da) was lost to form a ring, the compound belonged to benzoquinoline-type alkaloids. 8 When RDA fragmentation occurred, the compound belonged to protoquinoline-type alkaloids. 42 The characteristics of berberine-type alkaloids and furanquinoline-type alkaloids were the loss of CH 3 (15 Da) and C 2 H 6 (30 Da), respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the CH 2 O group (30 Da) was lost to form a ring, the compound belonged to benzoquinoline-type alkaloids. 8 When RDA fragmentation occurred, the compound belonged to protoquinoline-type alkaloids. 42 The characteristics of berberine-type alkaloids and furanquinoline-type alkaloids were the loss of CH 3 (15 Da) and C 2 H 6 (30 Da), respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…7 Rao et al found that the ZN extract could exert an anti-inflammatory effect by inhibiting the production of NO in Raw264.7 cells. 8 Due to its obvious anti-inflammatory effect, it is also used as an additive in toothpaste. 9 However, the plant resources of ZN are mainly dependent on the wild resources.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Because of the extensive sources and complex metabolites, it is difficult to determine the pharmacodynamic material basis of TCM ( Liang et al, 2022 ). Comfortingly, the spectrum–effect relationship has become an important tool for exploring the relationship between the pharmacological effects and the material basis of TCM ( Rao et al, 2022 ). It organically connects the fingerprint (active metabolites) and pharmacological data on TCM, and systematically reveals the relationship between them through a reasonable spectrum–effect model and analytical method ( Wang et al, 2019c ).…”
Section: Discussionmentioning
confidence: 99%
“…The spectrum-effect relationship of TCM adopts the combination of the “spectrum” of the chemical composition of TCM and the “effect” of the clinical action of TCM. Among them, the “spectrum” is mostly a fingerprint or feature atlas with holistic and fuzzy features; the “effect” is mostly an indicator that can represent the efficacy of TCM, which should have classical, parsimonious and sensitive features [ 18 , 19 ]. A simple chemical fingerprint cannot effectively assess the relationship between components and TCM efficacy, even though fingerprinting is a widely acknowledged quality evaluation approach of TCM in China.…”
Section: Introductionmentioning
confidence: 99%